Peran Terapi Reminiscence sebagai Upaya untuk Memelihara Fungsi Memori pada Lansia Yayasan Panti Asuhan Al-Hikmah - Siti Hikmah; Siti Syarah Nursuada; Fitri Nurul Hayani; Ishma Annisa (Observasi : Jurnal Publikasi Ilmu Psikologi, 2025)
Reminiscence therapy is a psychological treatment specifically designed for the elderly to improve mental health status by recalling and accessing memories that still exist. In addition to helping strengthen memories, reminiscence therapy also provides emotional benefits, such as increasing self-confidence, creating feelings of being valued, and building social bonds with fellow residents of the orphanage. The purpose of the intervention is to maintain memory function in the elderly of Al-Hikmah Orphanage Foundation using Reminiscence therapy. The method used is a combination of empowerment and capacity building to empower the elderly to recognize the potential and value of their life experiences. Based on the results of research conducted using pre-test and post-test, it can show that these elderly people still have clear memories of the past.